FEATURES OF ULTRASTRUCTURAL CHANGES IN THE LUNGS IN SEVERE COURSE OF COVID-19 INFECTION - Kuzyk, Yuliia; Semko, Marta; Dankovych, Roman (Eastern Ukrainian Medical Journal, 2024)
Introduction. An essential point in the pathogenesis of COVID-19 is endothelial dysfunction with the development of thrombosis and microangiopathy of pulmonary vessels, which is one of the causes of high mortality. At the same time, electron microscopic examination of the pulmonary vascular bed in COVID-19 coronavirus infection is rarely performed.Objective: To investigate ultrastructural changes in the pulmonary microcirculatory bed by determining the features of endothelial damage and the role of vascular disorders in the pathogenesis of severe COVID-19 coronavirus infection.Methods. The material was collected at autopsy, no later than 2 hours after the fact of death of patients, fixed in Millonig's fixative with pH 7.36. Dehydration was carried out in increasing-strength ethanol, transferred to propylene oxide, and tarred in a mixture of Araldite. Ultrathin sections with a thickness of 60 nμ were made using an LKB 2188 Ultrotome NOVA ultramicrotome. According to Reynolds, sections were mounted on support grids and contrasted with uranyl acetate and lead citrate. The obtained samples were viewed in a transmission electron microscope TEM 100-01, and photofixation was carried out using a KAPPA Image Base digital camera.Results. Significant structural changes in type 2 pneumocytes were observed with the development of degeneration and reactive hyperplasia, the formation of syncytial elements, dyscirculatory disorders with endothelial alteration, pronounced hyperemia and stasis, coagulopathy, and thrombosis. In the lumen of the alveoli, in addition to the deposition of fine-grained masses of fibrin hyaline membranes, fibrinous exudate, desquamated type 2 pneumocytes, macrophages, lymphocytes, plasma cells, single neutrophils, and erythrocytes were detected.Individual type 2 pneumocytes were characterized by the appearance of “giant lamellar bodies” measuring 2-4 μm, which occupied a significant part of the cytoplasm. Hyperplasia of type 2 pneumocytes was observed in some areas of the lung tissue. The proliferation of fibroblasts and collagen fibrils was detected in the interstitium of the interalveolar septa.Conclusions. As a result of transmission electron microscopy of the lungs of patients who died due to severe COVID-19 coronavirus infection, pronounced dyscirculatory changes were found in the vessels of the microcirculatory bed, characterized by the development of hyperemia, stasis, and microthrombosis with pronounced degenerative, necrotic changes in the endothelium and the development of endotheliitis